# :what are the solutions to the equation 3(x – 4)2 = 27? (1) 1 and 7 (3) 4 + 24 (2) -1 and -7 (4) – 4 + 24

C x = x = one-third

Step-by-step explanation:

What is the solution to the equation 3(x – 1) – 2(2x + 1) = 8(x – 1)?

x = x = negative StartFraction 4 Over 7 EndFraction

x = x = StartFraction 3 Over 7 EndFraction

x = x = one-third

x = x = two-thirds

no, the answer is x = 12

Step-by-step explanation:

3(x + 4)= 2x - (-2x)

3(x + 4)= 2x + 2x

3x + 12 - 12 = 4x - 12

3x - 4x = 4x - 12 - 4x

-x = -12

x = 12

Step-by-step explanation:

3x - 3 - 4x - 2 = 8x - 8

Solving like terms

-x - 5 = 8x - 8

Bringing like terms on one side

-5 + 8 = 8x + x

3 = 9x

3/9 = x

1/3 = x

x = 1/3

One-third

Step-by-step explanation:

3(x-1) -2(2x+1) = 8(x-1)

3x-3-4x-2=8x-8

-x-5=8x-8

Collect like terms

-x-8x=5-8

-9x=-3

Divide both sides by -9

x = 3/9

= 1/3

x = 1/3

Step-by-step explanation:

3(x - 1) - 2(2x + 1) = 8(x - 1)

3x - 3 - 4x - 2 = 8x - 8

-x - 5 = 8x - 8

-9x = -3

x = 1/3

x =

Step-by-step explanation:

Distribute parenthesis on both sides of the equation.

3x - 3 - 4x - 2 = 8x - 8 ← simplify left side

- x - 5 = 8x - 8 ( subtract 8x from both sides )

- 9x - 5 = - 8 ( add 5 to both sides )

- 9x = - 3 ( divide both sides by - 9 )

x = = =